Sea anemone venom: Ecological interactions and bioactive potential. (March 2022) - Menezes, Cecelia; Thakur, Narsinh L.
Abstract: This article provides a brief overview of the literature related to the chemical ecology of sea anemones, focusing on their venom, and summarizing their bioprospecting potential. Sea anemones have been known as a copious source of peptides and other molecules having bio-medical potential, however very little is known about the ecological role of these molecules. From an ecological prospect, these molecules are involved in prey capture, protection against predators, or deterring competitors of the sea anemone. Whereas, in bioprospecting, these toxic molecules have potential biotechnological applications. Herein, we present the diversity of sea anemone venom toxins reported to date and describe the role of venom in various chemically mediated ecological interactions of the sea anemone. This paves a path for continuing and broadening efforts to evaluate their functional and ecological importance. Graphical abstract: Image 1 Highlights: Toxins secreted by sea anemones have vital ecological roles like defense, offense, prey capture, larval recruitment, etc. Venom is a diverse cocktail of toxic peptides and non-proteinaceous molecules. These molecules can be developed to be therapeutically, agriculturally and industrially important compounds. There is great scope for studies to understand the chemical ecology of sea anemones and the ecological role of their toxins. It can pave the way for the discovery of novel and unexpected biotechnological applications.